Finding new Arabidopsis receptor kinases that regulate compatible pollen-pistil interactions - Bordeleau, Stephen J.; Canales Sanchez, Laura E.; Goring, Daphne R. (Frontiers in Plant Science, 2022)
Successful fertilization of a flowering plant requires tightly controlled cell-to-cell communication between the male pollen grain and the female pistil. Throughout Arabidopsis pollen-pistil interactions, ligand-receptor kinase signaling is utilized to mediate various checkpoints to promote compatible interactions. In Arabidopsis, the later stages of pollen tube growth, ovular guidance and reception in the pistil have been intensively studied, and thus the receptor kinases and the respective ligands in these stages are quite well understood. However, the components of the earlier stages, responsible for recognizing compatible pollen grains and pollen tubes in the upper reproductive tract are less clear. Recently, predicted receptor kinases have been implicated in the initial stages of regulating pollen hydration and supporting pollen tube growth through the upper regions of the reproductive tract in the pistil. The discovery of these additional signaling proteins at the earlier stages of pollen-pistil interactions has further elucidated the mechanisms that Arabidopsis employs to support compatible pollen. Despite these advances, many questions remain regarding their specific functions. Here, we review the roles of the different receptor kinases, integrate their proposed functions into a model covering all stages of pollen-pistil interactions, and discuss what remains elusive with regard to their functions, respective binding partners and signaling pathways.